FTO Genotype, Vitamin D Status, and Weight Gain During Childhood - Lourenço, Barbara H. (American Diabetes Association, 2014)
Previous evidence suggests that variants in the fat mass and obesity-associated gene (FTO) affect adiposity in an age-dependent fashion in children, and nutritional factors may modify genotype effects. We assessed the effect of FTO rs9939609 on BMI and BMI-for-age Z score changes during childhood in a population-based longitudinal study in the Brazilian Amazon and investigated whether these effects were modified by vitamin D status, an important nutritional factor related to adiposity. At baseline, 1,088 children aged <10 years had complete genotypic and anthropometric data; 796 were followed up over a median 4.6 years. Baseline vitamin D insufficiency was defined as <75 nmol/L. We observed a 0.07 kg/m(2)/year increase in BMI and a 0.03 Z/year increase in BMI-for-age Z score per rs9939609 risk allele over follow-up (P = 0.01). Vitamin D status significantly modified FTO effects (P for interaction = 0.02). The rs9939609 risk allele was associated with a 0.05 Z/year increase in BMI-for-age Z score among vitamin D–insufficient children (P = 0.003), while no significant genetic effects were observed among vitamin D–sufficient children. Our data suggest that FTO rs9939609 affects child weight gain, and genotype effects are more pronounced among children with insufficient vitamin D levels.